Derivação ventriculoatrial no tratamento da hidrocefalia em crianças - Almeida, Gilberto Machado De [UNESP] (Academia Brasileira de Neurologia - ABNEURO, 1969)
The interest for the surgical treatment of hydrocephalus has considerably increased in the last decade owning to the continuos development of the techniques for ventriculo-venous shunts. However, the occurrence of several complications lowered the initial enthusiasm of some neurosurgeons regarding this particular technique. Due to this fact we embarked upon a study for evaluation of the results in a series of 136 hydrocephalic children, operated upon between December 1958 and December 1965. Up to the present time (December-1967) a total of 72 children are alive, showing a compensated hydrocephalus and 30 patients died, being impossible to obtain a follow-up of the 34 remaining cases. After the analysis of the operatory conditions, of the complications and of the results, the folloying conclusions are withdrawn: 1) the ocurrence of pulmonary tromboembolic complications is quite rare after ventriculoatrial shunts, justifying the use of this technique for the treatment of hydrocephaly till others forms of treatment are available; 2) periodic cardiologic examinations should be performed in patients submitted to ventriculo-venous shunts in order to prevent right cardiac insuficiency; 3) the prevention of infectious complications and selection of the cases are fundamental for better post-operative results; 4) the physician responsible for treatment of hydrocephalic patients should warn the parents regarding the possibility of new sirguical interventions and be ready to re-operate as many times as necessary; 5) there is not justifycable the replacement of the atrial tube when its extremity reaches the level of the fourth thoracic vertebra; 6) there is not correct the assertion that an shunt has to remain always with the drainage process working fully; 7) in order to evaluate the prognosis of the mental development of the hydrocephalic patients, a group of data has to be considered as a whole, namely the neurological examination, cranial transilumination, etiology of the disease, electroencephalo-graphic tracings, Gesell test and, if possible, the measurement of the cerebral mantle; 8) a normal psychological development (IQ greater than 85) can be expected in about 40% of the patients with controled hydrocephalus.

Na última década, devido ao desenvolvimento das técnicas de derivação ventrículo-venosa, aumentou consideravelmente o interesse pelo tratamento cirúrgico da hidrocefalia. Entretanto, com o tempo, foram sendo observadas complicações que fizeram arrefecer o entusiasmo inicial de alguns cirurgiões. Julgamos oportuno, por isso, fazer uma avaliação dos resultados obtidos em uma série de 136 crianças hidrocefálicas operadas entre dezembro de 1958 e dezembro de 1965, e nas quais foi feita derivação ventrículo-atrial. Das crianças operadas, 72 estão vivas e com a hidrocefalia compensada e 30 faleceram, não sendo possível estabelecer as condições atuais das 34 restantes. A análise das condições pré-operatórias, das complicações e dos resultados finais permitiram algumas conclusões: 1) é pequena a ocorrência de manifestações clínicas de tromboembolismo pulmonar, no pós-operatório da ventrículo-atriostomia, justificando-se o uso destas derivações, enquanto não se desenvolverem formas mais eficazes de tratamento da hidrocefalia; 2) exames cardiológicos repetidos devem ser feitos em doentes submetidos às derivações ventrículo-atriais, a fim de permitir o diagnóstico precoce de sobrecarga do coração direito; 3) com enérgico tratamento das complicações infecciosas, progresso das técnicas de assepsia e seleção cuidadosa dos casos, os resultados tendem a melhorar; 4) o médico que trata hidrocefálicos deve prevenir os familiares a respeito da possível necessidade de novos atos cirúrgicos, devendo estar preparado para reintervir tantas vezes quantas forem necessárias; 5) não é justificada a conduta de trocar o catéter atrial sempre que a extremidade do mesmo atinge o nível da quarta vértebra torácica, como recomendam alguns cirurgiões; 6) não é justificada a afirmação de que uma criança submetida à ventrículo-atriostomia necessite permanecer sempre com a drenagem funcionando; 7) para avaliar o prognóstico quanto ao desenvolvimento mental dos hidrocefálicos. há necessidade de considerar em conjunto os elementos: exame neurológico, transiluminação do crânio, etiologia do processo, eletrencefalograma, teste de Gesell e, quando possível, a medida da espessura do pálio cerebral; 8) pode-se esperar desenvolvimento psíquico normal (QI acima de 85) em cerca de 40% dos doentes com hidrocefalia controlada.
Ventriculoatrial shunts in the treatment of hydrocephalus in children